The context of conflict resolution : international relations and the study of peace and conflict - Sousa, Ricardo Real P. (2018)
This paper provides a brief review of almost one century of academic research within the discipline of International Relations with a focus on the thinking about Peace and Conflict and its links to approaches in Conflict Resolution. The framework of analysis is based on the definition of science, what is studied and how it is studied, which delimits the analysis into the four debates in IR: between 1919 and the 1940s, the idealist versus realist debate; in the 1950s and 1960s, the traditionalist versus behaviourist debate; in the 1970s and 1980s, the inter-paradigm debate, and, since the 1990s, the rationalist versus reflectivist debate. This paper identifies how the classical conception of security centred on the state, the military and external threats was broadened by different approaches to include other actors (individuals, groups, societies, civilizations), other sectors (economic, political, social, environmental) and internal threats. In tandem, it maps the epistemological and sometimes ontological challenges to positivism and rationalism found in (Neo) Realism, (Neo) Liberalism and Marxism, by a set of post-positivist and reflective theories or approaches, such as the cases of Human Security, Feminism, Post-structuralism, Constructivism, Post-Colonialism, Critical Studies, and the Copenhagen School. The emergence and development of all these theories and approaches are historically contextualized alongside developments of Conflict Resolution approaches.